2016
DOI: 10.1111/pce.12704
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacteria activates (+)‐δ‐cadinene synthase genes and induces systemic resistance in cotton against beet armyworm (Spodoptera exigua)

Abstract: Gossypol is an important allelochemical produced by the subepidermal glands of some cotton varieties and important for their ability to respond to changing biotic stress by exhibiting antibiosis against some cotton pests. Plant growth-promoting rhizobacteria (PGPR) are root-colonizing bacteria that increase plant growth and often elicit defence against plant pathogens and insect pests. Little is known about the effect of PGPR on cotton plant-insect interactions and the potential biochemical and molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 57 publications
2
65
1
Order By: Relevance
“…Previous research suggests PGPR-mediated reduction of cucurbitacin C, which reduced beetle feeding damage, could also decrease attraction in foraging or ovipositing beetles [56]. In contrast, another study reported that cotton plants (Gossypium hirsutum) treated with PGPR had increased levels of the defense compound gossypol and increased expression of genes that regulate its production, resulting in decreased performance of beet armyworm larvae on PGPR plants [163]. As a generalist herbivore, beet armyworm may avoid PGPR-associated cotton plants with increased gossypol that reduce its performance.…”
Section: Influence Of Beneficial Microbes On Plant-produced Gustatorymentioning
confidence: 99%
“…Previous research suggests PGPR-mediated reduction of cucurbitacin C, which reduced beetle feeding damage, could also decrease attraction in foraging or ovipositing beetles [56]. In contrast, another study reported that cotton plants (Gossypium hirsutum) treated with PGPR had increased levels of the defense compound gossypol and increased expression of genes that regulate its production, resulting in decreased performance of beet armyworm larvae on PGPR plants [163]. As a generalist herbivore, beet armyworm may avoid PGPR-associated cotton plants with increased gossypol that reduce its performance.…”
Section: Influence Of Beneficial Microbes On Plant-produced Gustatorymentioning
confidence: 99%
“…and conferred ISR in loquat trees against Colletotrichum acutatum (Wang et al ). Zebelo et al () showed that Bacillus spp. conferred protection in cotton against Spodoptera exigua through higher gossypol accumulation which was again related with the activation of genes involved in JA defence signalling network.…”
Section: Induction Of Systemic Resistancementioning
confidence: 99%
“…Importantly, the effect of root‐associated microbes on herbivorous insects varies from positive (D'Alessandro et al ., ; Megali et al ., ) to negative (van Oosten et al ., ; Pangesti et al ., ; Zebelo et al ., ) and to date we do not fully understand the factors responsible for this variation. Biotic factors such as feeding guild and degree of specialization of the insects have been shown to affect the outcome of plant–microbe interactions.…”
Section: Introductionmentioning
confidence: 97%